Análisis comparativo de la misión en los bancos de la ciudad de Machala. - Barcia Farez, Pedro Alex (My University, 2019)
To understand the mission of the 12 Banks studied it is necessary to prepare a comparative analysis of the mission through a field investigation that identifies the degree of similarity and difference that exists in the Banks of the City of Machala. For this, a bibliographic review of the mission of each bank was carried out with the prior authorization and permission of the heads of agencies. The methodology used is a qualitative approach using the elementary properties of the mission, for which the inductive-analytical research method was used where an exploration was performed and each mission was examined was descriptive-explanatory because it allowed us to know the similarity and difference regarding the mission of each of the Banks studied. The first finding was that Banco Pichincha and General Rumiñahui demonstrated that they have a certain type of similarity with respect to their Mission, with three elementary properties of the mission that are: focused, differentiated and extended. Likewise, the second finding was that Banco Guayaquil showed that there is a difference with respect to the mission of the other Banks, because it only has two elementary properties that are: differentiated and brief. The results obtained show that the mission of some Banks in the city of Machala has similarities and differences, which is why the investigation of this case was very helpful in demonstrating and responding to the problems of the case.
Para comprender la misión de los 12 Bancos estudiados es necesario elaborar un análisis comparativo de la misión mediante las cinco propiedades elementales de la misión que identifique el grado de similitud y diferencia que existen en los Bancos de la Ciudad de Machala. Para ello se realizó una revisión bibliográfica de la misión de cada banco previa autorización y permiso de los jefes de agencias. La metodología que se utilizó es de enfoque cualitativo con la recopilación de información de la misión de los Bancos para lo cual se empleó el método investigación inductivo-analítico donde se realizó una exploración y se examinó cada misión fue de tipo descriptivo-explicativo porque permitió conocer la similitud y diferencia respecto al misión de cada uno de los Bancos estudiados. El primer hallazgo fue que el Banco Pichincha y General Rumiñahui demostraron que tiene cierto tipo de similitud respecto a su Misión contando con tres propiedades elementales de la misión que son: enfocada, diferenciada y amplía. Así mismo el segundo hallazgo fue que el Banco Guayaquil demostró que, sí existe diferencia respecto a la misión de los demás Bancos, debido a que solo cuenta con dos propiedades elementales que son: diferenciada y breve. Los resultados que se obtuvieron demuestran que la misión de algunos Bancos de la ciudad de Machala tiene similitudes y diferencias, es por ello que la investigación de este caso fue de gran ayuda para demostrar y dar respuestas a las problemáticas del caso.
Keywords: MISIÓN; BANCOS; PROPIEDADES ELEMENTALES DE LA MISIÓN; CLIENTES